Hubungan Tingkat Pengetahuan dengan Perilaku Mengatasi Efek Samping Kemoterapi pada Pasien Kanker Payudara di RSUD Prof. Dr. Margono Soekarjo Purwokerto - Sa'adah, Anirotus; Siwi, Adiratna Sekar; Haniyah, Siti (NHM PRESS, 2023)
Knowledge in undergoing chemotherapy affects behavior in carrying out the chemotherapy treatment process. Behavior in chemotherapy can be known through the extent to which the patient agrees with the medical advice given in terms of the behavior of carrying out therapy, changing lifestyle, and complying with the medical consultation schedule. This study aims to analyze the relationship between the level of knowledge and the behavior of overcoming chemotherapy side effects in breast cancer patients at RSUD Prof. Dr. Margono Soekarjo Purwokerto. The research method used in this study was correlation with cross sectional design. The population of all respondents who underwent chemotherapy was 62 patients according to the inclusion criteria. Sampling technique using total sampling. Data collection techniques using questionnaires, data analysis techniques using spearman rank. This research instrument uses a questionnaire of knowledge and behavior to overcome the side effects of chemotherapy in breast cancer patients. The results of the study showed that the level of knowledge mostly had a good category as many as 36 respondents (58.1%). Behavior mostly has a good category as many as 42 respondents (67.7%). Based on statistical test, the value of P value = 0.980 (P > 0.05) with correlation coefficient 0.003. The conclusion is that there is no relationship between the level of knowledge and the behavior of overcoming chemotherapy side effects in breast cancer patients at RSUD Prof. Dr. Margono Soekarjo Purwokerto.